Solution for 3x+4=2x-1 equation:
Simplifying
3x + 4 = 2x + -1
Reorder the terms:
4 + 3x = 2x + -1
Reorder the terms:
4 + 3x = -1 + 2x
Solving
4 + 3x = -1 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
4 + 3x + -2x = -1 + 2x + -2x
Combine like terms: 3x + -2x = 1x
4 + 1x = -1 + 2x + -2x
Combine like terms: 2x + -2x = 0
4 + 1x = -1 + 0
4 + 1x = -1
Add '-4' to each side of the equation.
4 + -4 + 1x = -1 + -4
Combine like terms: 4 + -4 = 0
0 + 1x = -1 + -4
1x = -1 + -4
Combine like terms: -1 + -4 = -5
1x = -5
Divide each side by '1'.
Your Answer is x = -5
Hope it helps!
OFFICIALLYQUEENZ
THANK YOU
Simplifying
x = -5